The Sair Kin Tambuan; A Banjarese versified version of a well-known Panji story - Wieringa, Edwin P.; Pudjiastuti, Titik (Wacana, Journal of the Humanities of Indonesia, 2020)
The Syair Ken Tambuhan (“Poem of Lady Tambuhan”) is a traditional Malay Panji tale in verse which is known in three redactions (short, middle, and long), all seeming to have a Sumatran origin, although an alternative hypothesis suggests that it might have originated from Borneo, in the Banjarmasin area. This article describes the hitherto unstudied Banjarese manuscript Sair Kin Tambuan from Kalimantan which represents the long redaction, running parallel to Klinkert’s 1886 edition which is based on a Riau manuscript. Probably copied in the twentieth century, since the mid-1980s it has been kept under call number N 4228 in the Museum Lambung Mangkurat in the town of Banjarbaru, South Kalimantan, Indonesia. Discussing a few variant readings, based upon comparisons with the text editions by Klinkert (1886) and Teeuw (1966), it is made clear that variae lectiones causing “philological alarm” are never “without value”, because problematic passages necessitate a close reading allowing analysts to delve deeper into the text.